The impact of three SMN2 gene copies on clinical characteristics and effect of disease-modifying treatment in patients with spinal muscular atrophy: a systematic literature review - Dosi, Claudia; Masson, Riccardo (Frontiers in Neurology, 2024)
Objective: To review the clinical characteristics and effect of treatment in patients with spinal muscular atrophy (SMA) and three copies of the SMN2 gene. Methods: We conducted a literature search in October 2022 to identify English-language clinical research on SMA that included SMN2 copy number according to PRISMA guidelines. Results: Our search identified 44 studies examining the impact of three SMN2 copies on clinical characteristics (21 on phenotype, 13 on natural history, and 15 on functional status and other signs/symptoms). In children with type I SMA or presymptomatic infants with an SMN1 deletion, three SMN2 copies was associated with later symptom onset, slower decline in motor function and longer survival compared with two SMN2 copies. In patients with SMA type II or III, three SMN2 copies is associated with earlier symptom onset, loss of ambulation, and ventilator dependence compared with four SMN2 copies. Eleven studies examined treatment effects with nusinersen (nine studies), onasemnogene abeparvovec (one study), and a range of treatments (one study) in patients with three SMN2 copies. In presymptomatic infants, early treatment delayed the onset of symptoms and maintained motor function in those with three SMN2 copies. The impact of copy number on treatment response in symptomatic patients is still unclear. Conclusions: SMN2 copy number is strongly correlated with SMA phenotype in patients with SMN1 deletion, while no correlation was found in patients with an SMN1 mutation. Patients with three SMN2 copies show a highly variable clinical phenotype. Early initiation of treatment is highly effective in presymptomatic patients with three SMN2 copies.